Asceticism and the Ethics of Consumption - Antonaccio, Maria (Journal of the Society of Christian Ethics, 2006)
IN THIS ESSAY I PRESENT NEW RESOURCES FOR THINKING ABOUT THE RElation between asceticism and ethics. The aims of the essay are threefold. The first is to highlight the work of scholars who interpret asceticism within the wider context of theories of moral formation and education in order to call attention to the cultural dimensions of asceticism. The second is to deploy ascetic concepts and tropes to analyze contemporary debates over the ethics of consumption and to suggest that asceticism may have surprising descriptive and diagnostic power in a culture marked by a pervasive consumerism. The third and final aim of the essay is to draw some of the constructive implications of this analysis for the debate over consumption and for the adequacy of naturalist versus nonnaturalist approaches to ethics.